A prática do professor de matemática permeada pela utilização da calculadora - Melo, Adenir Roberto Fernandes de (2008)
For decades, Mathematics teaching in Brazil has been experiencing changes, criticism and adaptations, aiming at reformulating educational practices used at schools so that they are in accordance with social changes and technological advances. In order to optimize time, sparing students from procedures that do not contribute to their real development, technological tools can serve as teaching resources in mathematics activities, one of which is the calculator. This study aims at getting to know the practice of mathematics teachers and researchers using the calculator in mathematics lessons and understanding what they consider important in this educational practice. As teachers of primary and secondary education (in both public and private schools) and researchers, who studied the topic calculators , were interviewed, four strands of analysis emerged that pointed the essential characteristics for and against the calculator in mathematics classes: motivation for use; forms of use; teacher training and challenges in using the calculator. These strands were interpreted based on the subjects, teachers, researchers and literature. From the analysis, it can be understood that the calculator has been used as a motivational tool in exploratory and discovery activities, error correction, results checking, self-evaluation and in challenging situations in which the student use it as a resource to resolve tasks. An additional finding was that, besides investing in teacher training, introducing technology such as the calculator in classes, depends very much on the interest of public policies in changing the conditions of schools and enabling the professional development of teachers